Space-Planning Solutions for Buildings of Existing Funds for Residential Buildings - Yunusov Shukurullo Khayrullayevich; Matkarimov Nuriddin Khusniddin ogli (Genius Journals, 2022)
This article provides an overview of the size and planning solutions of existing housing stock, as well as the functional layout of the rooms. An analysis of the architectural and planning solutions of the first two "generations" of large-panel residential buildings showed that they do not meet modern requirements at all. The shortcomings of the buildings are especially evident in the lack of long-term scheduled repairs. Nevertheless, the period under study led to the beginning of mass intensive construction of housing, aimed at improving the living conditions of millions of people.
Keywords: Construction; Roofing; Panel Building; Balconies